"Pollen tube shower" in Bertolonia (Melastomataceae): a new delayed selfing mechanism in flowers with poricidal anthers. (11th September 2021) - Passos, Luan Salles; Telles, Francismeire Jane; Goldenberg, Renato; Maia, Fabiano Rodrigo
Abstract: About one-fifth of angiosperms reproduce predominantly through self-fertilization, mediated by morphological and functional flower traits. Autonomous selfing is rare in Melastomataceae, a megadiverse family with most species featuring poricidal anthers and herkogamy. However, previous studies suggested that some Bertolonia spp. were capable of autonomous selfing. Here, we investigated the existence of autonomous selfing in the group and, considering its specialized floral morphology, the mechanisms involved in this process. We conducted studies on floral biology, pollination experiments and pollinator visitation rates for Bertolonia paranaensis (anthers with introrse pores) and Bertolonia mosenii (anthers with extrorse pores). The transient absence of herkogamy and the dynamics of the movements of the flower parts during post-anthesis events promoted delayed selfing in both species. In post-anthesis flowers, pollen grains germinate inside the anthers, the pollen tubes come out through the anther pores and then reach the stigma, penetrating the transmission tissue, and fertilize the ovules. Both species received visits from buzzing bees and have a mixed mating system, i.e. the capacity of cross-pollination and delayed selfing-pollination. We present the first description of an autonomous selfing mechanism for plants with poricidal anthers, for which we coin the name "pollen tube shower". Pollen tube shower promotes reproductive assurance to flowers that have not been pollinated and ensures reproductive success of individuals in the absence of pollinators.